M27 Bronchiectasis multicentre cohort; baseline demographics from BRONCHUK. (12th November 2019) - Brown, J; Bradley, J; Copeland, F; Carroll, M; Crichton, M; Duckers, J; Haworth, C; Floto, RA; Hill, AT; Loebinger, M; Wilson, R; Hurst, J; et al.
Abstract : Bronchiectasis is increasingly recognised but poorly described. There is variability in aetiology, management and outcomes. We have adapted the EMBARC platform and created a multisite UK based registry with affiliated biobank. The BronchUK partnership (www.bronch.ac.uk ) aimed to recruit 1500 adult patients with annual follow up over 3–5 years. We report our demographic data. Methods: Multicentre recruitment (13 secondary care sites) with databasing of patient demographics. Data is quality assured on a routine basis. We followed the EMBARC protocol for data collection including Quality of Life Bronchiectasis (QOL-B) and SGRQ questionnaires. Results: 1403 patients have been recruited. We report data on the first 813 with complete core datasets; 504 were female (62%), 309 male (38%). The mean age 65 years SD 12.6 (median is 67 IQR 61–73). Patients were predominantly Caucasian (93%). The majority were never smokers 478 (58.8%) or ex-smokers 304 (37.4%) with only 31 (3.8%) self-reporting current smoking. Morbidity was high; Cardiovascular disease was present in 234 (28.8%). 147 (18.1%) were hospitalised in the last year due to respiratory disease, 666 (81.9%) were not. Exacerbations were common with one – 144 (17.7%), Two – 144 (17.7%) three or more- 319 (39.3%). Only 206 (25.3%) reported no exacerbations in prior 12 months. Haemophilus influenzae was the most frequent organism isolated (19.1% of all patients/29.3% of patients producing baseline sputum). Pseudomonas was cultured in most recent sputum in 98 (12.1%) rising to 223 (27.4%) isolating Pseudomonas in the last 2 years. The mean BMI was 26.5 (22.3–29.3) and median, FEV1% predicted median 76.9 (59.1–95.1). The Bronchiectasis severity index (BSI) was - mild= 233 (29%), moderate= 391 (48%), severe= 189 (23%). Common aetiologies were idiopathic (40%) and post infectious (34%). COPD and Asthma were either common comorbidities or suspected aetiologies (16–21% and 3–39%) respectively. Conclusions: The BronchUK registry has a broadly representative cohort of patients in terms of simple demographics (female predominant, Haemophilus infections, idiopathic/post infectious aetiologies) but the morbidity levels and hospitalisation rates are noteworthy. Long term follow up will help us ascertain which patients are at highest risk of poor outcomes. Acknowledgements: MRC Funding grant MR/L011263/1, Recruiting sites and patients.